2021
DOI: 10.3390/vaccines9111336
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Attitudes towards Seasonal Influenza Vaccination in Poland: A Nationwide Cross-Sectional Survey in 2020

Abstract: We aimed to assess attitudes towards the influenza vaccine and factors associated with a willingness to vaccinate against seasonal influenza in Poland during the COVID-19 pandemic (flu season 2020/2021). This cross-sectional questionnaire-based study was carried out between 5 and 15 November 2020 on a representative nationwide sample of 1052 individuals aged 18+ in Poland. Of the respondents, 5.5% (95% CI: 4.3–7.0%) declared that they had already got vaccinated against influenza and 13.4% (95% CI: 11.4–15.6%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 16 publications
0
11
1
Order By: Relevance
“…Our results demonstrated that people concerned about COVID-19 infection decided to refuse influenza vaccination more often (OR = 1.65, CI 95% [1.02–2.66], Table 2 ). This result is in contrast to a recently published study performed by Samel-Kowalik et al in Poland on a group of 1052 individuals aged 18+, which found that respondents who cited negative attitudes toward COVID-19 vaccination were more often likely to cite a lack of willingness to vaccinate against influenza [ 30 ]. In addition, the statistical data showing influenza vaccination coverage rates worldwide do not confirm our finding [ 6 ].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our results demonstrated that people concerned about COVID-19 infection decided to refuse influenza vaccination more often (OR = 1.65, CI 95% [1.02–2.66], Table 2 ). This result is in contrast to a recently published study performed by Samel-Kowalik et al in Poland on a group of 1052 individuals aged 18+, which found that respondents who cited negative attitudes toward COVID-19 vaccination were more often likely to cite a lack of willingness to vaccinate against influenza [ 30 ]. In addition, the statistical data showing influenza vaccination coverage rates worldwide do not confirm our finding [ 6 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Nowadays, Polish healthcare authorities are making significant efforts to improve the convenience of influenza vaccination for the general public. For instance, to solve the problem of non-availability of influenza vaccines in pharmacies, public health authorities have increased the number of vaccines ordered from manufacturers [ 30 ]. Furthermore, in late 2021, legislative measures introduced free vaccines for all patients over 18 years of age, which may also be provided at pharmacies [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a retrospective analysis of the vaccination coverage rates in the general population in 19 EU/EEA Member States in 2016-2017 established that Poland is a country with one of the lowest influenza vaccination coverage rates, and the vaccination coverage rates in older target populations is also one in the lowest in the EU [35]. A study performed by Samel-Kowalik et al showed that, in November 2020 among adults in Poland, only 5.5% had already been vaccinated against influenza [36], even though adults aged 65 and over are covered by the free vaccination program. Taking into account such an unfavorable vaccination status, an increased risk of COVID-19 infection in the elderly population and a higher chance of severe illness or death due to COVID-19 complications, we therefore highlighted the importance of the influenza vaccine protective effect in Poland and other countries with low influenza vaccine coverage.…”
Section: Discussionmentioning
confidence: 99%
“…This justifies the need to understand various factors that may play a role in such a low interest in influenza vaccination in Poland. The representative study by Samel-Kowalik et al, conducted among Poles in 2020, found that among those aged over 60, low levels of religious practices and internet use were significantly associated with positive attitudes toward influenza vaccination [ 12 ].…”
Section: Introductionmentioning
confidence: 99%